A cognitive evaluation and equity-based perspective of pay for performance on job performance: A meta-analysis and path model - Chen, Yuyao; Zhang, Zhengtang; Zhou, Jinfan; Liu, Chuwei; Zhang, Xia; Yu, Ting (Frontiers in Psychology, 2023)
Pay for performance, as one of the most important means of motivating employees, has attracted the attention of many scholars and managers. However, controversy has continued regarding whether it promotes or undermines job performance. Drawing on a meta-analysis of 108 independent samples (N = 71,438) from 100 articles, we found that pay for performance was positively related to job performance. That pay for performance had a more substantial positive effect on task performance than contextual performance in workplace settings. From the cognitive evaluation perspective, we found that pay for performance enhanced employees' task performance and contextual performance by enhancing intrinsic motivation and weakened task performance and contextual performance by increasing employee pressure. From the equity perspective, our results indicated that the relationship between pay for performance and task performance was partially mediated by employee perceptions of distributive justice and procedural justice, with distributive justice having a more substantial mediating effect than procedural justice. However, the relationship between pay for performance and contextual performance was only partially mediated by procedural justice. Further tests of moderating effects indicated that the varying impacts of pay for performance are contingent on measures of pay for performance and national culture. The findings contributed to understanding the complex mechanisms and boundary conditions of pay-for-performance's effects on job performance, which provided insights for organizations to maximize its positive effects.